Fast food restaurant density and weight status: A spatial analysis among Filipina migrant workers in Macao (SAR), People's Republic of China. (January 2021) - Hall, Brian J.; Huang, Lei; Yi, Grace; Latkin, Carl
Abstract: Background: Female migrant populations are at high risk of being overweight or obese. Beyond individual risk factors, exposure to the neighborhood food environment may contribute to their unhealthy weight status in the host region. Incorporating spatial analysis, this study examined the association between exposure to fast food restaurants and unhealthy weight status among Filipina domestic workers in Macao (SAR), China. Methods and Findings : Data were collected from 1388 Filipina domestic workers recruited using respondent-driven sampling between November 2016 to August 2017. Self-reported data on demographic characteristics, residential mailing address, and health-related behaviors were collected using tablet devices. Height and weight were objectively measured at the study site. Restaurant locations and resident addresses were geocoded and integrated into a shapefile for residential locations using ArcGIS. Nearly 64% of participants were classified as being overweight or obese, with 25.02% overweight and 38.96% obese. Adjusted multivariable logistic regression indicated that increased fast food restaurant density within a 0.5-mile buffer zone around a residential address was positively associated with higher odds of being overweight and obese (aOR = 1.07; 95% CI [1.01–1.14]. Conclusions : Increased fast food restaurant density was associated with unhealthy weight status among Filipina domestic workers in Macao (SAR), China. Providing healthy working environment, including access to healthy food, is indicated to improve the health of this population. Keywords: overweight; obesity; migrant workers; fast food restaurant density; spatial analysis. Highlights: A total of 1388 Filipina migrant workers provided anthropometric data on obesity. Nearly 64% of participants were classified as being overweight or obese. Of these, 25% were overweight and 39% were obese. Higher fast food restaurant density associated with more overweight or obesity.